Genotype distribution of Chinese Mycoplasma bovis isolates and their evolutionary relationship to strains from other countries. (October 2017) - Menghwar, Harish; He, Chenfei; Zhang, Hui; Zhao, Gang; Zhu, Xifang; Khan, Farhan Anwar; Faisal, Muhammad; Rasheed, Muhammad Asif; Zubair, Muhammad; Memon, Atta Muhammad; Ridley, Anne; Robertson, Ian D.; et al.
Abstract: This study was undertaken to determine the genotypic distribution of Chinese M. bovis strains and their similarity to isolates from other countries. Two multilocus sequence typing (MLST) schemes (MLST-1 and MLST-2) and pulsed field gel electrophoresis (PFGE) were used to compare 44 Chinese strains and the M. bovis type strain PG45. The results showed a high genetic homogeneity of Chinese isolates; 43 of 44 (97.7%) Chinese isolates were identified as ST-10 and as ST-34 by MLST-1, while for MLST-2 42 of 44 (95.5%) were identified as ST-10 with the two remaining isolates of ST-32 and ST43. PFGE clustered 42 of 44 (95.5%) of the Chinese isolates into PT-I. The overall agreement rate between the three typing methods was 97.8% (95% CI:86.8–99.9%). The type strain PG45 was identified as a unique type by all three methods. When the MLST-2 scheme was further used to analyze 16 isolates of Australian and Israeli origin ST-10 was more dominant among Australian isolates (7/8), compared with those from Israel (3/8). The evolutionary relationship of the 60 isolates typed in this study assessed together with 206 additional isolates retrieved from pubmlst/mbovis database analyzed by geoBURST Minimum spanning tree (MST) confirmed that the Chinese, Israeli and Australian M. bovis isolates typed in this study that were predominantly ST-10, were clustered in CC3 with isolates originating from the USA. Our results suggest that ST-10 is an emerging clone of M. bovis population. We hypothesized that the widespread distribution of this type is a result of global livestock movements. These findings will help further the understanding of the global evolution of M. bovis and development of novel vaccines against M. bovis . Highlights: Forty-four Chinese M. bovis isolates and a reference strain PG45 were genotyped using two M. bovis MLST schemes and PFGE. Both MLST schemes identified 97.7% and 95.5 % Chinese isolates as ST-10, while PFGE clustered 95.5% Chinese isolates into PT-I. M. bovis population in China exists as one single dominant ST-10 clone, which is also present in Israel, Australia and USA. Five novel sequence types (ST-43, ST-41, ST-42, ST-44 and ST-45) were identified. Development of novel vaccine may be effective in controlling M. bovis associated diseases.